İslam hukukunda dinleri ve ülkeleri farklı olanlar arasında vasiyet ve miras hükümleri - Mutlu, Hatice (My University, 2004)
Çalışmamızın esasını din ve ülke farklılığının vasiyet ve mirasa etkisi oluşturmaktadır. Bu sebeple de konu, Devletler Özel Hukuku sahasına girmektedir. Fakat bununla ilgili olarak müstakil bir çalışma yapılmamıştır. Bu çalışmanın hazırlanmasında da bu husus dikkate alınmış, konuya genel bir çerçeve çizilmiştir. Sonucunda da din farklılığının vasiyete mâni olmadığı; ancak mirasa her iki taraf için de mâni olduğu görülmüştür. Bununla birlikte, farklı görüşler ve değerlendirmeler de yapılmaktadır. Fakat yukarıdaki görüşün temeli, vasiyetin bir çeşit teberru (iyilik) olmasına, iyiliğin de hangi dinden olursa olsun herkese yapılabileceğine; mirasın ise velâyete dayandığı ve farklı dinlere mensup insanlar arasında velâyetin bulunamayacağı esasına dayanmaktadır. Ülke farklılığının vasiyete etkisi ise tartışılmış, müslümanların böyle bir vasiyetle zarara sokulma ihtimalini göz önüne alanlarca ülke farklılığı vasiyete engel sayılmıştır. Ancak konu dikkatli incelendiğinde böyle bir ihtimalin yokluğu durumunda ülke farklılığının da vasiyete engel olmadığı görülmektedir. Ülke farklılığını mirasa engel sayanlar da ülkeler aralarında velâyet ve güvenliğin olmamasını delil getirirler. Fakat devletler velâyet ve güvenliğin sağlanması adına aralarında anlaşma yaparak karşılıklı miras hukukunu düzenleyebilirler. Bu durumda da ülke farklılığının mirasa mâni olma noktasında mutlak bir hüküm olmadığını görüyoruz. The wost important subject of my work is now effects of the difference religions and countries, to testament and innheritance . Because of that reasen the subject of my work interests countries private law. But there has not been a work about that subject up to now. While prepearing my work. I pay attention to that and I work the general points of this subject. At the result we understand dearly. To have teostament is impossible between the people who are from the different religions but to have inheritance is possible between that kind of people. The reason of that opinions is; testament depends on goodness and bless and goodness is for all the people who live on the world, who have different religions. Otherwise there has been different opinions about that. To have inheritance is depends on velâyet (the obligation with attantion depends on relative ship) and velâyet is impossible for the people who are from the different religions. The effect of difference of the countries for testament has been discusseol, by same academician and the difference about country has been seen obstacle for testament by the academician. Who defence the idea that the testament law from different countries is not suitible and useful for moslem coutntries people. But when we pay attention to this subject carefully we understand dearly; if there is no possibility like this, it is clear that the difference of the countries is not obstacle for testament. According to same academician, to have inheritance is not possible for the people who are from different countries. The reason of that is no security and no velâyet between the countries. But the goverments can order the inheritance law about that subjects buy making pacts with each other in that way. We can see that, difference of the countries is not obstacle for having inheritance.
Keywords: Hukuk, İslam